Five Love Languages and Personality Factors Revisited - Edwin Adrianta Surijah; Komala Sari (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2018)
Current research replicates previous research on five love languages. It aimed to gather further validation evidence and to determine whether a person with a particular love language has a certain personality type as well. Undergraduate students participated as research sample (n = 313). Love languages and personality types were measured with Five Love Languages scale and Big Five Inventory respectively. Zero-order correlation showed a significant correlation between love languages and personality types except on Receiving Gift and Neuroticism. Comparison with the previous research exhibited diverging result which prompts to discussions on a better approach to measuring love languages.